PERANCANGAN SISTEM INFORMASI AKUNTANSI BERBASIS FRAMEWORK CODEIGNITER PADA MASJID AN NUR KABUPATEN SANGGAU - Rahman Sastrawan; Chornolius Hendreo; Arief Rio Maulana (JURNAL LENTERA AKUNTANSI, 2024)
The mosque is a non-profit organization, whose income is based on voluntary donations from the community. The An Nur Mosque's financial management still uses conventional or manual methods. To improve accountable and transparent financial reporting, an accounting information system design was created that uses a website with the codeigniter framework method at the An Nur Mosque in Sanggau Regency, West Kalimantan. This research aims to develop an accounting information system that uses the codeigniter framework, with a focus on making it easier to prepare financial reports for the An Nur Mosque. The research method applied is descriptive qualitative with a waterfall method approach which includes various steps such as needs analysis, design, implementation and testing. The results of this research show that the design of an accounting information system can help non-profit organizations, especially the An Nur Mosque, in preparing more accurate and transparent financial reports.